Meningkatkan Kemampuan Menerapkan Prosedur Kombinasi Gerak Dasar Jalan, Lari, Lompat dan Lempar dengan Permainan Olahraga yang Dimodifikasi dan Olahraga Tradisional di Kelas V (lima) SDN 1 Sumengko Kecamatan Wringinanom Kabupaten Gresik - Santje Wulansari (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Sports and health physical education lessons are basically an integral part of the overall education system, aimed at developing aspects of health, physical fitness, critical thinking skills, emotional stability, social skills, reasoning and moral actions through physical and sporting activities. This study aims to: 1) Describe the activities of the teacher in improving the ability to apply a combination of basic road, running, jumping and throwing procedures with modified sports and traditional sports. 2) Describing the activities of students in learning activities increases the ability to apply the procedure of a combination of basic road, running, jumping and throwing with modified sports and traditional sports. 3) Describe learning with modified sports games and traditional sports in improving the ability to apply a combination of basic road, running, jumping and throwing procedures with modified sports and traditional sports. This research is a classroom action research conducted collaboratively. Designing problem situations, and ways to collaborate with children, is the main focus of meetings that occur between teachers and researchers. This research was conducted at Sumengko 1 Elementary School with the address Ds. Sumengko - Wringinanom- Gresik Postal Code: 61176 Tel. 031 8982812. The subjects of this study were Class V students (five) of 30 children. The study was conducted in odd semester 2018/2019 academic year, for 3 months (September, October, and November 2018). Procedures for cyclical action research are: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and nonstandard tests. Test instrument items with validity test, reliability test, calibration test (level of difficulty) and distinguishing test. the entire process of data analysis is interactive using the Miles and Huberman models with the final mix method analysis. The results of the study concluded: 1) The teacher's activity experienced an increase in Pre-Action getting 63.57 percent and increasing in Cycle I by 74.29 percent and increasing in Cycle II by 88.57 percent; 2) Activities of students experienced an increase in Pre-Action to obtain a result of 43.57 percent and increase in Cycle I by 65.71 percent and increase in Cycle II by 87.14 percent; 3) The average value of the test (Classical Absorption) has increased in Pre-Action to get 7 percent and increased in Cycle I by 7.51 percent and increased in Cycle II by 7.76 percent. Classical Learning Completion has increased in Pre-Action obtained 76.67 percent and increased in Cycle I by 83.33 percent and increased in Cycle II by 93.33 percent